Clinical Features and Risk Factors for Active Tuberculosis in Takayasu Arteritis: A Single-Center Case-Control Study - Zhou, Jiawei; Ji, Ruoyu; Zhu, Rui; Zhou, Jingya; Li, Jing; Tian, Xinping; Chen, Yuexin; Zheng, Yuehong (Frontiers in Immunology, 2021)
Backgrounds. Takayasu arteritis (TAK) is a chronic, granulomatous vasculitis correlated with tuberculosis (TB). The two diseases share similar pathological characteristics and clinical manifestations which increase the difficulty to diagnosis. Active tuberculosis (ATB) has implications for treatment strategies in TAK patients. Therefore, the investigation of clinical features and potential risk factors of ATB in TAK patients is vital. Methods. The study reviewed hospitalized patients diagnosed with TAK in our hospital from 2008, to 2021. TAK patients with ATB were enrolled as the case group. The control group was randomly selected in a 3:1 ratio. The clinical characteristics of TAK patients with and without ATB were compared. Multivariate logistic regression analysis was performed to determine risk factors for ATB in TAK patients. Results. We reviewed 1789 patients and ultimately identiﬁed 30 (1.7%) ATB cases. TAK patients with ATB were more prone to develop symptoms including fever (p=0.001), fatigue (p=0.003), cough (p=0.037), expectoration (p<0.001), weight loss (p=0.003) and night sweating (p<0.001). Increased level of hypersensitive C reactive protein (hsCRP, p=0.001), decreased level of albumin (p=0.031) and higher positive rate of T-SPOT.TB test (p<0.001) were observed in the case group. Multivariate logistic regression analysis revealed that hsCRP>8mg/L (OR 9.108; 95% CI, 1.096-75.711; p=0.041) and positive T-SPOT.TB result (OR 68.669; 95% CI, 7.291-646.738; p<0.001) were risk factors for ATB in TAK patients. The proportion of patients undergoing subsequent surgery for Takayasu arteritis was lower in patients with ATB (p<0.001). Conclusion. Our study suggested that the diagnosis of ATB should be considered when TAK patients experienced symptoms including fever, fatigue, weight loss, etc. hsCRP>8mg/L and positive T-SPOT.TB result were identified as independent risk factors for ATB in TAK patients.